Stock market prediction using ensemble learning - Rabbani, Rakin Bin; Amin, B. M. Fahad-ul; Khan, Sumaiya Tanjil; Mahbub, Farjiya Benta (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.